PENGARUH KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN TERHADAP KEPUASAN MASYARAKAT PADA KANTOR KECAMATAN KARANGAMPEL KABUPATEN INDRAMAYU: Impact of Administrative Service Quality in Population Affairs on Public Satisfaction at the Karangampel Subdistrict Office, Indramayu Regency - Dinar Novikasari; Rohadin Rohadin; Ade Setiadi (Universitas Wiralodra, 2025)
Population administration services are one of the essential public services provided by local governments to fulfill the basic rights of the community. This research aims to analyze the influence of service quality on community satisfaction at the Indramayu Regency Population and Civil Registration Service. SERVQUAL's five service quality dimensions—physical evidence, reliability, responsiveness, assurance, and empathy—were used as the basis for the analysis. The research method used is a quantitative approach with survey techniques of 100 service user respondents. The research instrument was tested through validity and reliability tests, while data analysis was carried out using multiple linear regression, partial tests, simultaneous tests, and coefficient of determination. The research results show that the five dimensions of service quality simultaneously have a significant effect on community satisfaction. Partially, the dimensions of reliability and responsiveness are the factors that have the greatest influence on service user satisfaction. The coefficient of determination shows that service quality explains most of the variation in people's satisfaction, while other factors such as previous service experience, cost perceptions, and supporting facilities also contribute. These findings emphasize that improving the quality of population administration services must be directed at accelerating the service process, increasing the accuracy of information, the competence of officers, and providing personal attention to service applicants. It is hoped that this research can be a strategic input in efforts to improve the public service system within the Indramayu Regency Dukcapil Office.